2020
DOI: 10.3390/v12050524
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Regulated Protein 78 Interacts with Zika Virus Envelope Protein and Contributes to a Productive Infection

Abstract: Zika virus (ZIKV; Flaviviridae) is a mosquito-borne flavivirus shown to cause fetal abnormalities collectively known as congenital Zika syndrome and Guillain-Barré syndrome in recent outbreaks. Currently, there is no specific treatment or vaccine available, and more effort is needed to identify cellular factors in the viral life cycle. Here, we investigated interactors of ZIKV envelope (E) protein by combining protein pull-down with mass spectrometry. We found that E interacts with the endoplasmic reticulum (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 87 publications
2
18
0
Order By: Relevance
“…Moreover, previous studies have reported chaperone protein GRP78 as an interacting protein of the E protein of other flaviviruses, namely DENV 21 24 and JEV 25 , 26 . More recently, GRP78 was identified as a protein that interacts with ZIKV E protein in pulldown experiments 67 , a result consistent with our identification of the same interaction in this study. Royle and colleagues also reported effects on ZIKV virus proteins and titers as a consequence of GRP78 depletion 67 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, previous studies have reported chaperone protein GRP78 as an interacting protein of the E protein of other flaviviruses, namely DENV 21 24 and JEV 25 , 26 . More recently, GRP78 was identified as a protein that interacts with ZIKV E protein in pulldown experiments 67 , a result consistent with our identification of the same interaction in this study. Royle and colleagues also reported effects on ZIKV virus proteins and titers as a consequence of GRP78 depletion 67 .…”
Section: Discussionsupporting
confidence: 93%
“…More recently, GRP78 was identified as a protein that interacts with ZIKV E protein in pulldown experiments 67 , a result consistent with our identification of the same interaction in this study. Royle and colleagues also reported effects on ZIKV virus proteins and titers as a consequence of GRP78 depletion 67 . In this study, the interaction between ZIKV E protein and GRP78 was confirmed by both co-immunoprecipitation and reciprocal co-immunoprecipitation in ZIKV infected cells, and the interaction was shown to occur for both ZIKV isolates examined.…”
Section: Discussionsupporting
confidence: 93%
“…BHK-21 cells were used to propagate SFV and CHIKV and were grown in Glasgow minimum essential medium (Thermo Fisher Scientific, Waltham, MA, USA) supplemented with 10% TPB, 10% FBS, and penicillin–streptomycin (final concentrations of 100 units/mL and 100 µg/mL, respectively) at 37 °C, 5% CO 2 . A549-NPro cells (a kind gift of R. E. Randall, University of St. Andrews, St. Andrews, UK) were grown in Dulbecco’s Modified Eagle’s medium (DMEM; Thermo Fisher Scientific, Waltham, MA, USA), supplemented with 10% FBS, 2 µg/mL puromycin, penicillin-streptomycin (final concentration 100 units/mL, 100 µg/mL, respectively); to grow and titrate ZIKV, puromycin was left out [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Protein samples were analyzed at Glasgow Polyomics on an LTQ-Orbitrap Elite instrument (Thermo Fisher Scientific, Waltham, MA, USA) coupled to UltiMate 3000 RSLCnano System chromatography system (Thermo Fisher Scientific, Waltham, MA, USA). Sample processing and analysis were carried out as previously described [ 47 ]. Interactors were identified using MaxQuant software and search conducted against UniProt database of Ae.…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon was observed clinically where COVID-19 patients had significantly higher expression of cell surface BiP (csBiP) in their alveolar epithelium ( Palmeira et al, 2020 , Aguiar et al, 2020 ). On the cell surface, BiP can facilitate viral attachment and entry such as for dengue virus ( Jindadamrongwech et al, 2004 , Chen et al, 2017 ), Japanese encephalitis virus ( Nain et al, 2017 ), Zika virus ( Pujhari et al, 2019 , Royle et al, 2020 ), coxsackievirus ( Triantafilou et al, 2002 ), Borna disease virus ( Honda et al, 2009 ), Ebola virus ( Reid et al, 2014 ), MERS-CoV, and bat coronavirus ( Chu et al, 2018 ). A recent computational study predicted that csBiP can bind SARS-CoV-2 ( Ibrahim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%